Nursing care in fast-track surgery strategy - Kozieł, Dorota; Stępień, Renata B.; Głuszek-Osuch, Martyna; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2015)
In recent years, many study results have been published confirming an improvement in the outcomes of treatment related with management of patients within the fast-track surgery programme. Early postoperative rehabilitation is possible provided there is engagement of a multi-disciplinary team, including well-educated nurses. Today, a diversion can be observed from traditional nursing on behalf of a coordinated, holistic approach, while more attention is paid to the, thus far marginalised, psychosocial aspects of care. The objective of the study is to discuss the basic assumptions of fast track surgery with respect to nursing care, with particular emphasis placed on the educational function. Modern nursing within the short-track surgery programme should focus on the provision of patients with care consisting of preliminary information concerning the perioperative period, social and psychological support, counselling in the area of home convalescence, and procedures in the case of complications.